2019
DOI: 10.1503/cmaj.181047
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced cervical cancer in a transgender man

Abstract: A 45-year-old transgender man presented to a gynecologist with a 2-year history of dysfunctional uterine bleeding. Vaginal bleeding had been occurring daily, small to moderate in volume, with periods of heavier irregular bleeding occurring without precipitating or alleviating factors. Additional symptoms included suprapubic discomfort managed with acetaminophen. The patient had attributed the cause of the persistent bleed to previous exogenous testosterone used for his hormonal gender confirmation, which he ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…Transgender patients may experience similar difficulties balancing gender identity and cancer risk as our patient did. A recent case report by Beswick et al describes a female-to-male transgender patient who is diagnosed with locally advanced cervical cancer after being counseled that he did not require screening for cervical cancer because of his sexual history [12]. This patient experienced unnecessary delays in diagnosis and treatment for his cancer due to his history and gender identity, similar to our patient with KS.…”
Section: Discussionsupporting
confidence: 54%
“…Transgender patients may experience similar difficulties balancing gender identity and cancer risk as our patient did. A recent case report by Beswick et al describes a female-to-male transgender patient who is diagnosed with locally advanced cervical cancer after being counseled that he did not require screening for cervical cancer because of his sexual history [12]. This patient experienced unnecessary delays in diagnosis and treatment for his cancer due to his history and gender identity, similar to our patient with KS.…”
Section: Discussionsupporting
confidence: 54%
“…Além disso, um estudo demonstra que indivíduos transgêneros e profissionais da saúde apresentam pouco conhecimento relacionado ao risco de infecção por HPV e câncer cervical (Agénor et al, 2016). Isso se mostra prejudicial ao processo saúde-doença dos homens transgêneros, pois afeta diretamente a procura pelos serviços de saúde, situação essa que se encontra relatada na literatura (Beswick, Corkum, & D'Souza, 2019), resultando em falta de rastreamento e identificação tardia de neoplasias.…”
Section: Rastreamento Do Câncer Cervical Em Homens Transgênerosunclassified
“…Over 90% of FTM transgender persons retain their cervices after transitioning and still require comprehensive gynecologic care, including cervical cancer screening 23 . Various studies have shown that FTM persons are less likely to obtain gynecologic care and cite emotional and psychological distress, negative healthcare experiences, mistreatment at health facilities and refusal of services based on their gender identity 24 26 . This is especially problematic given that FTM persons are at a higher risk for undetected HPV infection and subsequent cervical cancer 23 .…”
Section: Introductionmentioning
confidence: 99%